1994
DOI: 10.1210/endo.134.2.7905409
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptors in the rat hypothalamus and pituitary.

Abstract: Although several recent anatomical and physiological studies indicate that glutamate receptors are likely to play a role in the regulation of various hypothalamic functions, no attempt has yet been made to specifically characterize glutamate receptor densities, subtypes, or localization in the hypothalamus. To provide this basic information, we have characterized and mapped the binding of [3H]glutamate to N-methyl-D-aspartate (NMDA), non-NMDA, and metabotropic glutamate receptors throughout the diencephalon. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(78 citation statements)
references
References 26 publications
3
74
0
1
Order By: Relevance
“…The presence of both NMDA and AMPA receptors in the DMH is well established by a variety of techniques, including receptor binding (Meeker et al, 1994), electrophysiology (Bailey et al, 2003), and pharmacological studies (Soltis and DiMicco, 1991;Bailey and DiMicco, 2001;Goren et al, 2003) (see also Introduction). However, the functional roles of the different glutamate receptors in the DMH appear to be much more complex.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of both NMDA and AMPA receptors in the DMH is well established by a variety of techniques, including receptor binding (Meeker et al, 1994), electrophysiology (Bailey et al, 2003), and pharmacological studies (Soltis and DiMicco, 1991;Bailey and DiMicco, 2001;Goren et al, 2003) (see also Introduction). However, the functional roles of the different glutamate receptors in the DMH appear to be much more complex.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, an inhibitory effect at pituitary level, an increase in dopamine release or a decrease in the secretion of hypothalamic PRFs might be responsible for the inhibitory effect of AMPA. Despite the presence of AMPA receptors in pituitary gland (Kiyama et al 1993, Meeker et al 1994, Bhat et al 1995, Villalobos et al 1996, the only pituitary effect observed was a weak stimulatory action after incubation of hemipituitaries with 10 8 M AMPA. The results strongly suggest that the activation of AMPA receptors does not affect the secretion of PRL via a pituitary mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…Current research is occupied with trying to elucidate which subunit combinations are found in which parts of the brain and trying to understand why neurons employ different subtypes of receptor. Binding of subtype specific agonists and antagonists for each major EAA receptor subtype is present in all hypothalamic and preoptic regions with relative densities NMDA > metabotropic receptor > kainate and AMPA (Meeker et al 1994). Receptor autoradiography reveals regional densities of EAA receptors to be ventromedial, dorsal medial> paraventricular, anterior hypothalamic, supraoptic> arcuate, suprachiasmatic, lateral hypothalamic > pre-optic area (Meeker et al 1994).…”
Section: MD Brown School Of Sport and Exercise Sciences University Omentioning
confidence: 99%